Is delay in application a factor that reduces efficacy of 1-Methylcyclopropene response in pears? - Calvo, Gabriela (2012)
Trabajo presentado al IV International Conference Postharvest Unlimited 2011. Leavenworth, Washington (Estados Unidos), Mayo 2011